Bio efficacy of methanol leaf extracts of Cissampelos pareira Linn., Lantana camara Linn. and Ocimum gratissimum Linn. against fever in Wistar rats - Kimuni Susan Nyawira; Gitahi Stephen Maina; Ngugi Mathew Piero; Njagi Eliud Mwaniki (Acta Marisiensis - Seria Medica)
This study evaluated antipyretic potency of methanol extracts of Cissampelos pareira, Lantana camara and Ocimum gratissimum in Wistar rats.